PENGARUH JUMLAH SUDU TURBIN ANGIN HORISONTAL TERHADAP KINERJA DALAM PEMBANGKIT LISTRIK SKALA MIKRO - Ismail Kholid; Mohammad Alexin Putra (BAROMETER, 2022)
Wind power plant is a power plant that uses renewable energy, namely wind energy. This study tested micro-scale wind power plants using a horizontal type wind turbine with a diameter of one meter with variations in the number of blades, namely 16 blades, 14 blades, 12 blades and 10 blades at wind speeds of 4.7 m/s, 4.1 m/s. , 3.6 m/s and 3 m/s. The purpose of this study was to determine the effect of the number of horizontal wind turbine blades on the turbine rotation with the load and electrical power generated. This research uses an experimental method and is divided into 3 stages, the first stage is the design of research tools and components, the second stage is making research tools and components, the third stage is testing. Based on the results of testing using a load, a wind turbine with 16 blades produces the highest turbine rotation, which is 47 rpm at a wind speed of 4.7 m/s and produces the highest electrical power, which is 0.12 W at a wind speed of 4.7 m/s.